EVALUATION OF ROUTE PERFORMANCED AND OPTIMIZATION OF PUBLIC TRANSPORT OPERATIONAL POLICY (CASE STUDY : TRANSJAKARTA) - ANGGRAYANI, RENI
Problems in urban areas such as DKI Jakarta consist of increasing urbanization, increasing traffic jams, constructing new roads that are not solutive and providing public transportation that is not yet optimal. This creates problems in the development of the public transportation network system, especially in Transjakarta Corridor 1. These problems are consist of a high utilization factor and the existence of two modes operating in one lane, namely Transjakarta Corridor 1 and MRT Jakarta Phase 1. Therefore, this study conducting an evaluation study and optimization of the Transjakarta route performance about impact of the MRT Jakarta construction. This study aims to evaluate of the Transjakarta route performance due to the impact of the MRT Jakarta construction in accordance with the performance indicators of public transport routes and optimize the evaluation results so as to produce alternative public transport policies in 2025 and 2035. This research was conducted using PTV Visum with the headway-based assignment method. There are 4 alternative policies evaluated, they are eliminating Transjakarta in Corridor 1, changing the type of bus Transjakarta Corridor 1, combination of decreasing the Transjakarta Corridor 1’s headway and changing the type of bus and combination of increasing the Transjakarta Corridor 1’s headway and changing the type of bus. Based on the impact model consist of users and operators, the chosen alternative policy is the combination policy of increasing the Transjakarta Corridor 1’s headway and changing the type of bus. The results of this policy resulted in an increase in MRT passengers by 2% and a decrease in Transjakarta corridor 1 passengers by 15-30%. However, the load factor achieved is able to match the ideal condition, that is 70% with a lower limit of > 50% and an upper limit of < 95, so it can be said to be optimal. The decrease in capacity also has implications for the decrease in BOK in Transjakarta corridor 1. On the other hand, by maintaining Transjakarta corridor 1, user needs can be facilitated by choosing 2 modes of public transport without planning to return to using private vehicles.